Combined Treatment (Ultraviolet-C/Physapruin A) Enhances Antiproliferation and Oxidative-Stress-Associated Mechanism in Oral Cancer Cells - Sheng-Yao Peng; Ching-Yu Yen; Ting-Hsun Lan; Jiiang-Huei Jeng; Jen-Yang Tang; Hsueh-Wei Chang (Antioxidants, 2022)
Physapruin A (PHA), a Physalis peruviana-derived withanolide, exhibits antiproliferation activity against oral and breast cancer cells. However, its potential antitumor effects in combined treatments remain unclear. This investigation focused on evaluating the impact of the combined treatment of ultraviolet-C with PHA (UVC/PHA) on the proliferation of oral cancer cells. The UVC-caused antiproliferation was enhanced by combination with PHA in oral cancer (Ca9-22 and CAL 27) but not normal cells (SG), as evidenced by ATP detection, compared with UVC or PHA alone. UVC/PHA showed a greater extent of subG1 increase, G2/M arrest, annexin-V-assessed apoptosis, caspase 3/7 activation, and reactive oxygen species (ROS) in the UVC or PHA treatment of oral cancer compared to normal cells. Moreover, the mitochondrial functions, such as mitochondrial superoxide bursts and mitochondrial membrane potential destruction, of oral cancer cells were also enhanced by UVC/PHA compared to UVC or PHA alone. These oxidative stresses triggered γH2AX and 8-hydroxyl-2’-deoxyguanosine-assessed DNA damage to a greater extent under UVC/PHA treatment than under UVC or PHA treatment alone. The ROS inhibitor N-acetylcysteine reversed all these UVC/PHA-promoted changes. In conclusion, UVC/PHA is a promising strategy for decreasing the proliferation of oral cancer cells but shows no inhibitory effect on normal cells.